A Reliability Generalization Meta-Analysis of "What Is Happening in This Class?" (WIHIC) Questionnaire - Cherry Zin Oo; Myint Swe Khine; Nang Mo Hline San (MDPI AG, 2022)
What is Happening In this Class? (WIHIC) is the widely used questionnaire to measure psycho-social aspects of the classroom and explore how these aspects affect student learning and achievement. The purpose of this study is to examine the cumulative estimates of reliability and conduct reliability generalization meta-analysis of Cronbach's alpha for the WIHIC questionnaire. PRISMA framework is used to identify the papers in three major databases. Assuming a random-effects model, the average internal consistency reliability was 0.85, 95% CI [0.83; 0.87] for total scores and ranged from 0.80 to 0.88 for subscales. There was a substantial heterogeneity among the included articles (I2 = 99.04%, Q (23) = 1481.074, p < 0.001). According to mixed model analysis, school context has a significant effect on the total scale and subscales, including teacher support, involvement, investigation, cooperation, and equity. Overall, the reliability generalization analysis of pooling reliability estimates helps in understanding the psychometric properties of the WIHIC inventory in diverse populations.